Petroleum Development In Malaysia: The Fiscal Regime - Krishnan, A (Journal of Malaysian and Comparative Law, 2019)
Apart from a sound general legislative structure to support a petroleum development programme in a country, the particular provisions in relation to overall financial considerations assume great importance, both from the point of view of the host government and that of the prospective investing company, though their objectives may not necessarily coincide.